Karakteristik fisikokimia kamaboko dengan penambahan garam rumput laut: Physicochemical characteristics of kamaboko with the addition of seaweed salt - Shoffiati Chaerul Ummah; Tatty Yuniarti; Nurjanah Nurjanah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2023)
Seaweed salt is a low-sodium salt innovation from Indonesian tropical seaweed that has the potential to prevent hypertension and is an added ingredient in food preparation. One of the innovations of seaweed salt can be applied to diversified fishery products, such as kamaboko. Kamaboko is a form of processed surimi that has high economic value and contains many nutrients that are beneficial to the body. This study aimed to determine the optimal concentration of added seaweed salt in the processing of kamaboko products based on physicochemical parameters. The kamaboko produced in the study consisted of four concentrations of added salt: 1.5 addition of consumption salt, 1.5 % seaweed salt, 3% seaweed salt, and 4.5% seaweed salt. Data were analyzed using ANOVA and Kruskal–Wallis tests. The results showed that kamaboko with different seaweed salt concentrations had significantly different effects on sensory parameters (appearance, smell, taste, and texture), hedonic properties (appearance, color, aroma, and taste), ash content, protein, lipid, NaCl, potassium, and the Na:K ratio. Kamaboko with the addition of 3% seaweed salt concentration was chosen as the best treatment based on the results of the panelist's assessment of sensory and level of preference with liking criteria: moisture content 69.95%, ash 2.66%, protein 10.44%, lipid 1.09%, carbohydrates 15.86%, crude fiber 0.80%, NaCl content 1.48%, potassium 530.81 mg/100 g, and Na:K ratio of 0.98.